Rice Straw-Derived Biochar Mitigates Microcystin-LR-Induced Hepatic Histopathological Injury and Oxidative Damage in Male Zebrafish via the Nrf2 Signaling Pathway - Wang Lin; Fen Hu; Wansheng Zou; Suqin Wang; Pengling Shi; Li Li; Jifeng Yang; Pinhong Yang (Toxins)
Microcystin-leucine arginine (MC-LR) poses a serious threat to aquatic animals during cyanobacterial blooms. Recently, biochar (BC), derived from rice straw, has emerged as a potent adsorbent for eliminating hazardous contaminants from water. To assess the joint hepatotoxic effects of environmentally relevant concentrations of MC-LR and BC on fish, male adult zebrafish (Danio rerio) were sub-chronically co-exposed to varying concentrations of MC-LR (0, 1, 5, and 25 μg/L) and BC (0 and 100 μg/L) in a fully factorial experiment. After 30 days exposure, our findings suggested that the existence of BC significantly decreased MC-LR bioavailability in liver. Furthermore, histopathological analysis revealed that BC mitigated MC-LR-induced hepatic lesions, which were characterized by mild damage, such as vacuolization, pyknotic nuclei, and swollen mitochondria. Compared to the groups exposed solely to MC-LR, decreased malondialdehyde (MDA) and increased catalase (CAT) and superoxide dismutase (SOD) were noticed in the mixture groups. Concurrently, significant changes in the mRNA expression levels of Nrf2 pathway genes (cat, sod1, gstr, keap1a, nrf2a, and gclc) further proved that BC reduces the oxidative damage induced by MC-LR. These findings demonstrate that BC decreases MC-LR bioavailability in the liver, thereby alleviating MC-LR-induced hepatotoxicity through the Nrf2 signaling pathway in zebrafish. Our results also imply that BC could serve as a potentially environmentally friendly material for mitigating the detrimental effects of MC-LR on fish.